Evaluation of the Islamic Education Student’s Books for the Lower Basic Stage in Jordan According to the Contemporary Criteria for the Environmental Education - Abo-glion, Eid Ismail Abed Rabbo (Arab Journal for Sciences and Research Publishing, 2016)
This study aimed to Abstract Evaluation of the Islamic Education Student’s Books for the Lower Basic Stage in Jordan According to the Contemporary Criteria for the Environmental Education, the study sample consisted of the same study population, the Islamic Education Textbooks of basic upper stage the Ministry of Education for the academic year 2015/2016. In order to achieve the objectives of the study, researcher developed measuring instrument, and the analysis included nine axles, and twenty-seven standard contemporary environmental Educational basic stage, has been the tool presented to the committee of judges who specialize in the curriculum, and the environment; to make sure of the sincerity, then the researcher process analysis, where was assigned to one of the teachers, who holds a master’s degree in curriculum and methods of teaching Islamic education to do the analysis process, too. reliability factor has been extracted using holsti equation (Holsti) for stability, reaching reliability coefficient over time (%89.7), and through the people (%86.8) and this parameter is acceptable for the purposes of the study, frequencies, percentages were used, and the study’s results revealed the low availability of contemporary standards of environmental education in those books.. In light of the findings, the researcher recommended : Including the environmental dimension in the books of Islamic education for the higher stage of basic education in Jordan, to enter information and concepts of environmental, or linking content appropriate environmental issues The lower basic stage, contemporary.